Eligibility for interventions, co-occurrence and risk factors for unhealthy behaviours in patients consulting for routine primary care: results from the Pre-Empt study. Issue 1 (December 2015) - Randell, Elizabeth; Pickles, Timothy; Simpson, Sharon; Spanou, Clio; McCambridge, Jim; Hood, Kerenza; Butler, Christopher
Abstract Background Smoking, excessive drinking, lack of exercise and a poor diet remain key causes of premature morbidity and mortality globally, yet it is not clear what proportion of patients attending for routine primary care are eligible for interventions about these behaviours, the extent to which they co-occur within individuals, and which individuals are at greatest risk for multiple unhealthy behaviours. The aim of the trial was to examine 'intervention eligibility' and co-occurrence of the 'big four' risky health behaviours – lack of exercise, smoking, an unhealthy diet and excessive drinking – in a primary care population. Methods Data were collected from adult patients consulting routinely in general practice across South Wales as part of the Pre-Empt study; a cluster randomised controlled trial. After giving consent, participants completed screening instruments, which included the following to assess eligibility for an intervention based on set thresholds: AUDIT-C (for alcohol), HSI (for smoking), IPAQ (for exercise) and a subset of DINE (for diet). The intervention following screening was based on which combination of risky behaviours the patient had. Descriptive statistics, χ2 tests for association and ordinal regressions were undertaken. Results Two thousand sixty seven patients were screened: mean age of 48.6 years, 61.9 % female and 42.8 % in a managerial or professional occupation. In terms of numbers of risky behaviours screened eligible for, two was the most common (43.6 %), with diet and exercise (27.2 %) being the most common combination. Insufficient exercise was the most common single risky behaviour (12.0 %). 21.8 % of patients would have been eligible for an intervention for three behaviours and 5.9 % for all four behaviours. Just 4.5 % of patients did not identify any risky behaviours. Women, older age groups and those in managerial or professional occupations were more likely to exhibit all four risky behaviours. Conclusion Very few patients consulting for routine primary care screen ineligible for interventions about common unhealthy behaviours, and most engage in more than one of the major common unhealthy behaviours. Clinicians should be particularly alert to opportunities to engaging younger, non professional men and those with multi-morbidity about risky health behaviour. Trial registration ISRCTN22495456